Factors Affecting Anemia in Pregnancy Women in Ibeju-Lekki, Lagos State, Nigeria - Olusesan Oyewole Oyerinde PhD; Essien Annieye Nkanga PhD; Ifeoluwa Emmanuel Oyerinde MSc; Onamade Akintoye PhD; Ifeoluwa Asekun-Olarinmoye PhD; Quadri Kunle Alabi PhD (SAGE Publishing, 2023)
Anemia progresses due to low red blood cells counts or hemoglobin. The World Health Organization (WHO) has suggested the condition to be a serious global public health problem that affects pregnant women worldwide. Anemic pregnant women may suffer post-partum hemorrhage, pre-term delivery, seizures, and severe cases of anemia that potentially lead to cardiac failure or death. However, it is pertinent for pregnant women and health service providers to have the adequate knowledge about the factors associated with anemia in pregnancy. Thus, this study assessed the factors associated with anemia in pregnancy women attending primary healthcare (PHC) centers in Ibeju-Lekki Local government area, Lagos state. This study employed descriptive cross-sectional design using multi-stage sampling method to recruit 295 pregnant women into the study. Data were collected using a semi-structured, self-administered questionnaire. The recruited participants (56.6%) were majorly in their third trimester, of which their mean age was 28.7 ± 5.9 years. About 80.7% of the participants were married, having a mean knowledge score of 6.6 ± 3.2. More than half of respondents (56.3%) were anemic and had a poor knowledge (50.5%) of anemia in pregnancy. The mean hemoglobin concentration within the population was 11.06 ± 0.73 g/dl with a range of 8.3 to 12.0. There was no significant association between the respondents' knowledge of anemia in pregnancy and anemic status (X 2  = 0.549; P  = .45). However, this study observed a significant association between dietary diversity score and anemic status (X 2  = 8.66; P  = .01) and the trimester status of respondents' first antenatal visit (X 2  = 9.603; P  = .008). The study concluded that anemia in pregnancy was associated with maternal factors such as their first antenatal visit and the dietary diversity score. Due to this, proper education of pregnant women on anemia by health workers during antenatal clinics or visits should be prioritize to improve their anemia status.